Functional materials based on metal hydrides - Li, H.; Zhu, M.; Buckley, Craig; Jensen, T. (MDPI AG, 2018)
Storage of renewable energy remains a key obstacle for the implementation of a carbon free energy system. There is an urgent need to develop a variety of energy storage systems with varying performance, covering both long-term/large-scale and high gravimetric and volumetric densities for stationary and mobile applications. Novel materials with extraordinary properties have the potential to form the basis for technological paradigm shifts. Here, we present metal hydrides as a diverse class of materials with fascinating structures, compositions and properties. These materials can potentially form the basis for novel energy storage technologies as batteries and for hydrogen storage.